2011
DOI: 10.4081/reumatismo.2009.48
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of foot structural damage in rheumatoid arthritis: clinical evaluation by validated measures and serological correlations

Abstract: tità del danno a carico delle strutture podaliche ha un andamento in genere variabile, talvolta ad evoluzione progressiva, con manifestazioni dipendenti dalle sedi anatomiche interessate, dall'età del soggetto affetto, ma in particolar modo dal grado di aggressività della malattia. In questo contesto, la determinazione del fattore reumatoide (FR) e, soprattutto, degli anticorpi anti-citrullina (anti-CCP) rappresentano, alla luce di numerose evidenze in letteratura, dei validi indici non solo diagnostici ma anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Only 10% had a supinated or very supinated foot posture. Similar results were reported by Biscontini et al [ 27 ] who studied the foot structure of 78 patients with RA using the FPI and observed that 65.4% of them presented with a pronated posture, and 34.6% had a supinated posture. In the present sample, the frequency of pronated and supinated feet was lower.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Only 10% had a supinated or very supinated foot posture. Similar results were reported by Biscontini et al [ 27 ] who studied the foot structure of 78 patients with RA using the FPI and observed that 65.4% of them presented with a pronated posture, and 34.6% had a supinated posture. In the present sample, the frequency of pronated and supinated feet was lower.…”
Section: Discussionsupporting
confidence: 89%
“…This deformity is often present in healthy adults, especially women, with an estimated prevalence of 23% [ 35 ]. Some authors have quoted higher figures (84.6%), employing the Manchester scale for hallux abductus valgus (23.1% mild, 37.2% moderate, 24.4% severe) [ 27 ]. Total frequency is similar to that obtained in this study, although the percentage of moderate and severe cases is lower.…”
Section: Discussionmentioning
confidence: 99%
“…Our results can be compared to the results of Biscontini at al. in 2009 [21], where after using the FPI and the Manchester Hallux Valgus they concluded that patients with RA can frequently present with hallux valgus and pronated foot. Both studies agree that feet of patients with RA suffer from a valgus pathology and forefoot deformity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the study by Gonzalez-Fernandez [53] reported a higher percentage of flattened footprint and pronated FPI in people with RA compared to the control group, although they also highlighted that they found more supinated feet in the RA group than in the control group. Biscontini et al [57] reported 65.4% of pronated feet, suggesting this foot position is more frequent in patients with AR. This disagrees with the data obtained in this study, where FPI values corresponded to a normal foot.…”
Section: Discussionmentioning
confidence: 95%